The Impact of Using Reading for Meaning Strategy Toward Student’s Reading Comprehension - Umar, Umar; Suparman, Suparman (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-JanuaryDO - 10.24843/e-jl.2022.v16.i01.p11, 2021)
This study was aimed at finding out the student’s  reading comprehension by using reading for meaning strategy of the eleventh grade students of SMAN 1 Lape in academic year 2020/2021.The method of this research was an experimental research. The participants of this research were the eleventh grade students of SMAN 1 Lape academic year 2020/2021. The sample of this researh are consisted 32 of students  in the control class and 31 students in the experimental class. The data collection of this research was pre test and post test. Then, data was analyzed by using SPSS. The reseult of this research was student’s reading comprehension by using reading for meaning strategy of the eleventh grade students of SMAN 1 Lape in academic year 2020/2021 wa significant. Futhermore, the mean score of the reading comprehension ability of the students taught by using conventional strategies of the eleventh grade students of SMAN 1 Lape was 78.87. There was a significant difference between the reading comprehension ability of the students taught by using reading for meaning strategy and that of the students taught by using conventional strategies of the eleventh grade students of SMAN1 Lape.